NGHIÊN CỨU CHẾ TẠO VÀ ĐÁNH GIÁ KHẢ NĂNG CHỐNG ĂN MÒN CỦA SƠN LÓT POLYVINYL BUTYRAL VL02.VN - Hà, Hữu Sơn; Nguyễn, Thị Yến; Lê, Quốc Phẩm; Nguyễn, Văn Vinh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDYING ON MANUFACTURING AND EVALUATING ANTI-CORROSION OF POLYVINYL BUTYRAL PRIMER VL02.VN Anti-corrosion primer based on polyvinyl butyral resin and zinc chromate pigment with many great advantages of mechanical strength, physical properties as well as chemical resistance is widely used in aviation and marine industries. In this article, we report the results from studying suitable materials for producing the primer. The produced VL02.VN primer has a viscosity of 1 mm, a bending strength of 1 mm, an impact strength greater than 100 kg.cm, and protecting steel background against salt spray during 168 hours. This study also indicates that the quality of VL02.VN paint is as well as the same type of paint manufactured by the Russian Federation.